2010
DOI: 10.1063/1.3429354
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dynamical anomalies of a Gaussian core fluid: A mode-coupling theory study

Abstract: We present a theoretical study of transport properties of a liquid comprised of particles interacting via Gaussian Core pair potential. Shear viscosity and self-diffusion coefficient are computed on the basis of the mode-coupling theory, with required structural input obtained from integral equation theory. Both self-diffusion coefficient and viscosity display anomalous density dependence, with diffusivity increasing and viscosity decreasing with density within a particular density range along several isotherm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 51 publications
(170 reference statements)
1
19
0
Order By: Relevance
“…At T = T th , however, RPA works poorly around r = 0, as expected from Eq. (15). On the other hand, RPA's results perfectly match with the simulation results at larger r 's including the first shell peaks.…”
Section: B High Temperature Regimesupporting
confidence: 77%
See 2 more Smart Citations
“…At T = T th , however, RPA works poorly around r = 0, as expected from Eq. (15). On the other hand, RPA's results perfectly match with the simulation results at larger r 's including the first shell peaks.…”
Section: B High Temperature Regimesupporting
confidence: 77%
“…Recently, thermodynamic and transport anomalies of the fluid phase in the vicinity of the reentrant peaks are investigated. 10,[12][13][14][15][16] Microscopic and structural properties such as the static structure factor in the fluid phase are also reported and documented. 6,7,9,11 These studies revealed that, as the density increases beyond the reentrant peak but at a fixed temperature, thermodynamic and structural properties of GCM becomes more ideal-gas-like, signaled by the lowering of the peak of the structure factors and the better agreement with simple approximations such as the random phase approximation (RPA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We numerically study the monodisperse GCM in three dimension and show that nucleation is suppressed at very high densities and that the system exhibits canonical glassy behavior in the supercooled state. The quantitative agreement of the dynamical properties with the theoretical predictions is better than that of all previously investigated model glass formers.The thermodynamic and dynamic properties of the GCM have recently been vigorously investigated [5,9,[12][13][14]. Most previous studies, however, focused on the density regime ρσ 3 1, where the phase diagram exhibits reentrant melting.…”
mentioning
confidence: 99%
“…The thermodynamic and dynamic properties of the GCM have recently been vigorously investigated [5,9,[12][13][14]. Most previous studies, however, focused on the density regime ρσ 3 1, where the phase diagram exhibits reentrant melting.…”
mentioning
confidence: 99%